Spectrophotometric Determination of Manganese in Wine by Oxidizing Acid Fuchsin - Liu, Ying-Hong; Zhan, Hong-wei; Heng, Li-juan; Ma, Wei-Xing (Asian Journal of Chemistry, 2012)
A new method was developed for the determination of manganese. The method is based on the oxidation of the reagent acid fuchsin by manganese(VII), which lead to the decoloration of the reagent. Determination of manganese was carried out by spectrophotometry after manganese with different valence being oxidized to Mn(VII) in the presence of sodium bismuth. Beer's law was obeyed from 0-1.3 μg/mL of Mn(VII) concentration with the apparent molar absorption coefficient of 2.52 × 104 L mol-1 cm-1. This method was satisfactorily used for the determination of trace manganese in wine samples.